Founding fathers funnies - Bagge, Peter 1957- (Dark Horse Books, 2016)
This books collect short vignettes featuring some of the country's best-known historical figures and some lesser-known ones
"This volume collects the Founding fathers funnies strips that first appeared in Apocalypse nerd issues #1-#6 (2005, 2006, 2007) and Dark Horse presents volume 2, #27 (2013), plus new strips"--Title page verso
Keywords: Geschichte 1783-1815; Founding Fathers of the United States / Comic books, strips, etc; Statesmen / United States / Comic books, strips, etc; Revolutionaries / United States / Comic books, strips, etc; Geschichte; Founding fathers; United States / History / Revolution, 1775-1783 / Comic books, strips, etc; United States / History / Confederation, 1783-1789 / Comic books, strips, etc; United States / History / 1783-1815 / Comic books, strips, etc; USA; Comic; Humoristische Darstellung